Increasing fruit set of 'Red Bartlett' pears in Southern Brazil - Brighenti A.F.* (2010)
The poor fructification is a serious problem of pear production in Brazil. The lack of fertilization, especially during blooming time, result in a poor fruit set and in a low yield of the orchard. When the pollination is poor, it is necessary to use bioregulators. The goals of the present study was to evaluate the effect of different products on fruit set of Red Bartlett (Pyrus communis L.) pears. The experiment was conducted in São Joaquim city (28deg;17'S, 49deg;56'W), Santa Catarina State. The experimental design was a randomized block design. The rate of fruit set was determined two months after the application of the products. The treatments were: 1 - Control (water); 2 - Boron (2000 mg L-1) + Kymon Plus® 2 ml L-1 (N - 9%, K - 3%, amino acids), applied at the beginning, full and end of the bloom; 3 - GA 3 (30 mg L-1) at full bloom; 4 - ANA (3.4 ml ha -1) + Prohexadione-Ca (500 mg L-1) at the beginning of the bloom + Promalin® (0.3 ml L-1) applied at the beginning and the end of the petals fall; 5 - Prohexadione-Ca (2500 mg L-1) at the petals fall; 6 - Prohexadione-Ca (5000 mg L-1) at the petals fall; 7 - Promalin® (0.3 mg L-1) at full bloom; 8 - Promalin® (1 mg L-1) at full bloom; 9 - Retain® (4000 mg L-1) 15 days after the full bloom; 10 - GA3 (40 mg L-1) + Paclobutrazol (0.2 mg L-1) at full bloom. The best results on fruit set were obtained with the following treatments 8 - Promalin (1 mg L-1), 7 - Promalin (0.3 mg L-1) and 10 - GA3 (400 mg L-1) + Paclobutrazol (0.2 mg L-1) at full bloom.